Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $H$ be a Hilbert space over $\mathbb{C}$. Let $\phi_{j} \in H$ and let $c_j$ be scalars. Prove that there exists a representation $$f=\sum_{j}c_{j}\langle f,\phi_{j}\rangle\phi_{j}, \forall f\in H$$ if and only if $$\|f\|^2=\sum_{j}c_{j}|\langle f,\phi_{j}\rangle|^2, \forall f\in H$$

My queries: For $\implies$: $\|f\|^2= \langle f,f \rangle = \sum_{i,j} c_{i} \overline{c_{j}} \langle f,\phi_{i} \rangle \overline{\langle f,\phi_{j} \rangle}\langle \phi_{i}, \phi_{j}\rangle$. It can not be simplified further due to $\phi_{j}$ are may not be orthogonal. Even if one assumes orthogonality it would become $\|f\|^2=\sum_{j}|c_{j}|^2|\langle f,\phi_{j}\rangle|^2\|\phi_{j}\|^2$ which is still not the desired form. Is there any way to apply the fact that the representation for $f$ is valid for "all" $f$ in some way to deduce the desired equality?

For sufficiency I intend to apply the polarization identity to $\langle f,\phi_{j}\rangle$ then substitute it into the desired formula for $f$, but the polarization identity implied $\langle f,\phi_{j} \rangle =0$ which is not true in general, is there any point I have missed?

share|improve this question
add comment

1 Answer

up vote 0 down vote accepted

If $f=\sum_{j}c_{j}\langle f,\phi_{j}\rangle\phi_{j}$, then $$ \|f\|^2=\langle f,f\rangle=\langle \sum_{j}c_{j}\langle f,\phi_{j}\rangle\phi_{j},f\rangle =\sum_{j}c_{j}\langle f,\phi_{j}\rangle\,\langle\phi_{j},f\rangle=\sum_jc_j|\langle f,\phi_j\rangle|^2 $$ (the series distributes with respect to the inner product because we are assuming it is a norm limit).

Conversely, if $\|f\|^2=\sum_jc_j|\langle f,\phi_j\rangle|^2$, then we have $$ \langle f,f\rangle = \sum_{j}c_{j}\langle f,\phi_{j}\rangle\,\langle\phi_{j},f\rangle =\langle \sum_{j}c_{j}\langle f,\phi_{j}\rangle\phi_{j},f\rangle $$ for all $f$. Using polarization, we get, for a fixed $f$ and any $g$ $$ \langle f,g\rangle = \langle \sum_{j}c_{j}\langle f,\phi_{j}\rangle\phi_{j},g\rangle. $$ So $f=\sum_{j}c_{j}\langle f,\phi_{j}\rangle\phi_{j}$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.